Pengaruh Gaya Kepemimpinan, Kompensasi, Dan Motivasi Kerja Terhadap Semangat Kerja Karyawan Pada Dinas Pendidikan Kota Kediri - Sita Nurmatus Salma; Indah Yuni Astuti; Ririn Wahyu Arida (Jurnal Manajemen Bisnis Era Digital, 2025)
Work enthusiasm is one of the efforts that can be made to optimize employee performance. There are several important factors that can affect employee work enthusiasm, including leadership style, compensation, and work motivation. This study aims to determine the effect of leadership style, compensation, and work motivation on employee work enthusiasm at the Kediri City Education Office. The research method used is a quantitative approach through Likert scale data. The sample in this study amounted to 69 respondents taken from the total number of employees using saturated sampling techniques. The analysis technique in this study is multiple linear analysis, t-test, and f-test processed using SPSS software version 25. The results of the study prove that leadership style, compensation, and work motivation partially have a significant effect on work enthusiasm. Also, simultaneously leadership style, compensation, and work motivation have a significant effect on employee work enthusiasm.